Landscape dynamics triggered by different economic systems: an example of LANDSAT satellite data applicability - Donša, Daša; Kaligarič, Mitja; Škornik, Sonja; Pipenbaher, Nataša; Grujić, Veno Jaša; Davidovič, Danijel; Žiberna, Igor; Ivajnšič, Danijel (Journal for Geography, 2020)
Ensuring sufficient productivity growth is central to economic development. However, these process leaves behind characteristic environmental footprints which differ between economic systems driven by different political ideologies. To assess such landscape-level political-economic impacts, a homogeneous cultural landscape, shared by countries with different land use management systems, must be studied. The Trilateral Park Goričko-Raab-Örség represents an ideal investigation polygon for such research questions. In this paper, the time-sequences of LANDSAT satellite multi-spectral imagery were applied to calculate landscape change dynamics represented with spectral change magnitude and direction variables. The results show significant differences in both indicators, between countries (or political-economic systems) and between studied time intervals (1984-1992, 1992-2007, 2007-2020), despite the fact that, after the collapse of socialism in Yugoslavia and real-socialism in Hungary, there were no radical changes in land use or parcel ownership. Our findings have an addition value, since such an objective methodological approach can be practically transferred to all politically marginal areas that share a homogeneous cultural landscape and leave behind different spatial footprints.
Keywords: CVA; Goričko-Raab-Örség; LANDSAT; PCA; landscape change; spectral change